Grape seed flour intake decreases adiposity gain in high-fat-diet induced obese mice by activating thermogenesis. (November 2019) - Zhou, Fang; Yin, Manwen; Liu, Yiwen; Han, Xue; Guo, Jielong; Ren, Chenglong; Wang, Wei; Huang, Weidong; Zhan, Jicheng; You, Yilin
Graphical abstract: Highlights: Grape seed flour decreases weight gain and cold tolerance in diet-induced mice. Body weight was reduced via enhancing energy expenditure. Attuned energy balance is highly related with brown adipose tissue thermogenesis. The beige adipocytes formation also play an important part in energy metabolism. Abstract: During the last decades, a dramatic global rise in the prevalence of obesity has become evident. Therefore, effective therapeutic approaches are necessary to help combat this condition. Grape seed is known as a rich source of biologically active polyphenols, which can be used as one of the candidates to resolve problems associated with obesity. This paper investigated the anti-obesity effects of grape seed flour (GSF) and showed that GSF ameliorated weight gain, hepatic lipid levels and part of the serum profiles. Moreover, GSF increased energy expenditure (EE) and thermogenesis in brown adipose tissue (BAT) in high-fat diet (HFD) induced obese mice. GSF also affected expressions of uncoupling protein 1 ( UCP1 ) and other metabolism-related genes in white adipose tissue (WAT). In conclusion, our results showed that GSF prevented diet-induced obesity in C57BL/6J mice, and suggested that the mechanism responsible was related to the promotion of energy metabolism.